Toward a Comprehensive and Integrated Strategy of the European Marine Research Infrastructures for Ocean Observations - Dañobeitia, Juan Jose; Pouliquen, Sylvie; Johannessen, Truls; Basset, Alberto; Cannat, Mathilde; Pfeil, Benjamin Gerrit; Fredella, Maria Incoronata; Materia, Paola; Gourcuff, Claire; Magnifico, Giuseppe; Delory, Eric; del Rio Fernandez, Joaquin; et al. (Frontiers in Marine Science, 2020)
Marine ecosystems are vital for life on Earth. Global change is progressing rapidly, and geo-hazards, such as earthquakes, volcanic eruptions and tsunamis, cause large losses of life and have massive worldwide socio-economic impacts. Enhancing our marine environmental monitoring and prediction capabilities will increase our ability to respond adequately to major challenges and efficiently operate early-warning systems. Research Infrastructures (RIs) are large-scale facilities encompassing instruments, resources, data and services used by the scientific community to conduct high-level research in their respective fields. The development and integration of marine environmental RIs as European Research Infrastructure Consortia (ERICs) is the response of the European Commission (EC) to global marine challenges through research, technological development and innovation. These infrastructures (EMSO ERIC, Euro-Argo ERIC, ICOS-ERIC Marine, LifeWatch ERIC and EMBRC-ERIC) include specialized vessels, fixed-point monitoring systems, Lagrangian floating buoys, test facilities, genomics observatories, bio-sensing and Virtual Research Environments (VREs), among others.